The collaborative process developed among pre- and in-service teachers within a continuing teacher education program - Brum, Maísa Helena; Ticks, Luciane Kirchhof (Acta Scientiarum. Language and Culture, 2015)
Current paper discusses the collaborative process developed between a pre- and an in-service teacher of English Language within a continuing teacher education program at a public school in Santa Maria, Rio Grande do Sul State, Brazil. The collaborative research investigation (MAGALHÃES; FIDALGO, 2008) focused on the interactions established between the participants in the development of English Language classes, which were prepared based on the concept of language as social practice (MOTTA-ROTH, 2008) for Grade Five students of the primary school, taking into account students’ needs and specificities. Lessons were recorded and transcriptions became the corpus of the research. The analysis revealed the collaborative process through the incorporation by the participants of traditional pre-established roles: a leading role undertaken by the in-service teacher, and a supporting role performed by the pre-service teacher, due to their hierarchical position within the apprenticeship and trainee system. However, the analysis also showed that the supporting role by the pre-service teacher enhanced a more dialogical collaborative process to the English classes, since her teaching contributions increased students’ participation and stimulated their production in the activities proposed.